Credit score: Assessing a library course's association with graduation rates and GPAs for at-risk students at a regional public university. Issue 3 (2nd October 2021) - Espe, Troy W.; Dettman, David M.; Noltze, Marv; Harnett, Daniel
Abstract: This study determined if a library credit course potentially influenced grades and graduation rates at a regional public university. The authors analyzed data from 33, 882 undergraduates who attended University of Wisconsin-Stevens Point between 2004 and 2018. To compare grade point averages (GPAs) and graduation rates, the authors separated data into two cohorts: students who passed Library Resources 101 and students who did not take the course. The study found virtually no difference in GPAs. However, students who completed the course graduated 18.5% more frequently than non-completers. The most extensive of its kind, this study adds depth to previous publications assessing library credit courses' statistical relationships with student success, especially at-risk undergraduates.